Regional differences in the prevalence of arterial hypertension in Croatia - Erceg, Marijan (Array, 2009)
Summary: This paper analyzes the Croatian Adult Health Survey data, collected in 2003 with a total of 9,070 respondents aged 18+. Based on an average of two measurements, respondents with the mean systolic arterial pressure ł140 mmHg or mean diastolic pressure ł90 mmHg were classified as hypertnesive. The data for men and women were analyzed separately, according to regions. Prevalence of hypertension in men was 40.5% (95% confidence interval CI 37.9–43.01; coefficient of variability CV=3.2), women 34.9% (95% CI 33.2–36.7; CV 2.5). There were no significant differences in regional prevalence in men, except in the Northern and Eastern region. In women we did not detect any significant regional difference. Non-controlled arterial hypertension is an important public health problem in all monitored regions of Croatia. Raising awareness about the problem, early detection and encouraging the population to adhere to the therapy for elevated arterial pressure, in addition to a healthy life style, are important for successful control and harm reduction